2022
DOI: 10.3897/zookeys.1083.78233
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Asiatic shrew of the genus Chodsigoa (Soricidae, Eulipotyphla, Mammalia) from the Dabie Mountains, Anhui Province, eastern China

Abstract: Asiatic shrews of the genus Chodsigoa (Soricidae, Eulipotyphla) currently comprise nine species, mostly occurring in southwest China. From May 2017 to August 2020, 11 specimens of Chodsigoa were collected from the Dabie Mountains in Anhui Province, eastern China. Their morphology was compared with other species within the genus and one mitochondrial (cytochrome b) and two nuclear (apolipoprotein B and breast cancer 1) genes were sequenced to estimate the phylogenetic relationships of these specimens. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In this study, both the morphological and molecular analyses in- (Shen et al, 2019), which act as dispersal corridors to facilitate the dispersal of terrestrial small mammals (Chen et al, 2022). Thus, the ancestor of B. bowersi and B. latouchei possibly migrated via the southeastern hills to eastern China, a potential migration route supported by several studies (Aplin et al, 2011;Ge et al, 2021).…”
Section: B Bowersimentioning
confidence: 52%
“…In this study, both the morphological and molecular analyses in- (Shen et al, 2019), which act as dispersal corridors to facilitate the dispersal of terrestrial small mammals (Chen et al, 2022). Thus, the ancestor of B. bowersi and B. latouchei possibly migrated via the southeastern hills to eastern China, a potential migration route supported by several studies (Aplin et al, 2011;Ge et al, 2021).…”
Section: B Bowersimentioning
confidence: 52%
“…Many studies have shown a high level of species diversity in the tribe Nectogalini. For example, two new species of the genus Chodsigoa (Kastschenko, 1907) were recently described ( C. hoffmanni and C. dabieshanensis ) (Chen et al, 2017 , 2022 ). Some subspecies, such as Chodsigoa furva (Anthony, 1941), Chimarrogale leander (Thomas, 1902), and Neomys milleri (Mottaz, 1907) were recommended species status (Burgin & He, 2018 ; Chen et al, 2017 ; Igea et al, 2015 ; Yuan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…All Cyt b sequences were aligned and examined, and screening for heterozygote nuclear gene fragments was performed in Mega 5 [24]. Referring to research articles on the same species [15,[18][19], we used the three nuclear genes concatenated to analysis. Based on the amplified sequences in this study and downloaded sequences from NCBI, phylogenetic analyses were conducted on the following two datasets: 1) Cyt b genes; 2) three nuclear genes concatenated.…”
Section: Sequence Analysesmentioning
confidence: 99%
“…[15], Chen et al . [1819], we amplified a mitochondrial gene (Cyt b ) and three nuclear gene fragments (Apob, Brca1, Rag2). Herein, we explore the phylogenetic relationships and taxonomic status of these species based on molecular and geometric morphometric data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation